Directions for Indonesian Language Policy in Education: Towards A Translingual Perspective (NOBEL: Journal of Literature and Language Teaching, 2022)
This study overviews literature regarding the development of Indonesian, language endangerment, language attitudes, and ideologies, as well as emerging teaching methodologies to provide the context of the current challenges facing Indonesia’s sociolinguistic situation. The establishment of Bahasa Indonesia as the national language helped unite the country but, at the same time, created new challenges for addressing linguistic diversity. The dissemination of English education has complicated the situation further and has been associated with exacerbating inequalities. These inequalities have not only had consequences for linguistic diversity but also for access to employment and education. Language policies continue to treat language as static rather than dynamic processes which involve one’s communicative repertoire. We argue that while some language scholars studying Indonesia have begun to acknowledge the advantages of translingual/multilingual education, there still remains under-addressed obstacles to its successful implementation and the risk of co-option for ulterior purposes. We conclude that advocacy for language policy in Indonesia should be a part of a broader effort to address the needs of marginalized communities and harness students’ diverse and dynamic linguistic repertoires to improve the quality of learning and inclusivity in the classroom